2021
DOI: 10.1080/23311916.2021.1944015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Epoxy/Clay Composite Coatings on an X65 Steel Substrate

Abstract: This paper presents the results of a combined experimental and theoretical study of the interfacial and mechanical properties of epoxy/clay composites coatings on a mild steel substrate. This was studied using nano-indentation and Brazil Disk techniques to determine the Young's moduli, hardness values and mode mixity characteristics of the composite coatings. The Young's moduli of the reinforced composites comprising 1, 3, and 5 wt. % of montmorillonite clay particles are shown to improve, respectively, by abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The degradation of materials due to corrosion constitutes a signi cant threat to people, the environment, company assets and reputation. Recent data from Association of Materials Protection and Performance (AMPP) indicate that the global annual cost of steel corrosion is $ 2,500 billion, emphasizing the urgent need for cost-effective corrosion control practices 1,[18][19][20][21][22][23][24] . Conventional corrosion inhibitors used for inhibiting corrosion of oil and gas production and transportation facilities are made from long chain (C12-C18) nitrogenous organic materials, mainly, aliphatic fatty acids derivatives, imidazolines and derivatives, quaternaries, and rosin derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of materials due to corrosion constitutes a signi cant threat to people, the environment, company assets and reputation. Recent data from Association of Materials Protection and Performance (AMPP) indicate that the global annual cost of steel corrosion is $ 2,500 billion, emphasizing the urgent need for cost-effective corrosion control practices 1,[18][19][20][21][22][23][24] . Conventional corrosion inhibitors used for inhibiting corrosion of oil and gas production and transportation facilities are made from long chain (C12-C18) nitrogenous organic materials, mainly, aliphatic fatty acids derivatives, imidazolines and derivatives, quaternaries, and rosin derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The results observed that the mechanical properties of the polymer improved after strengthening it with threedirections Kevlar fibers, and the values of these properties increased with the increase in the percentage of added fibers [14]. Kusmonon The measured mechanical properties showed an increase with the increasing weight ratio of clay [18]. Zahra Khalid Hamdan et al (2021), used waste natural composite materials as base materials to manufacture a novel composite.…”
Section: Introductionmentioning
confidence: 99%